2016
DOI: 10.1002/biof.1281
|View full text |Cite
|
Sign up to set email alerts
|

Circulating leptin and NF‐κB activation in peripheral blood mononuclear cells across the menstrual cycle

Abstract: Using the menstrual cycle as a model, this study focused on longitudinal changes and associations within a physiological network known to play a role in female fertility, including, as biologically active nodes, NF-jB, leptin and adiponectin, bcarotene, adipose tissue, and progesterone. In 28 women, leptin, adiponectin, b-carotene, and progesterone concentrations, NF-jB p65 and p50 activation in peripheral blood mononuclear cells (known to possess estrogen, progesterone and leptin receptors), total body fat (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Previous studies have determined that there are higher leptin levels during the luteal phase than the follicular phase, and that leptin levels rise steadily throughout the menstrual cycle [8,27]. We found that leptin levels were higher (albeit not significantly so) during ovulation than during menses [8], but we further found that estradiol was a stronger predictor during menses than at ovulation.…”
Section: Resultssupporting
confidence: 46%
“…Previous studies have determined that there are higher leptin levels during the luteal phase than the follicular phase, and that leptin levels rise steadily throughout the menstrual cycle [8,27]. We found that leptin levels were higher (albeit not significantly so) during ovulation than during menses [8], but we further found that estradiol was a stronger predictor during menses than at ovulation.…”
Section: Resultssupporting
confidence: 46%
“…As the second important finding for the proposed role of arginine in modulating immune functions for successful pregnancy, plasma arginine concentrations for the first time were identified, by using regression analysis, as predictors of the activation of the NF-κB p65 subunit in PBMC at late follicular phase, linking arginine to the role of NF-κB p65 in the immune response shift required for materno-fetal immune tolerance. So far, NF-κB p65 activation in PBMC was shown to be decreased in pregnancy [ 20 ], as well as to decline from follicular to luteal phase of the menstrual cycle, while associations with arginine or progesterone concentrations have not been reported [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For determination of the activation of the NF- κ B p65 subunit, blood was collected in BD Vacutainer® CPT TM tubes (Becton, Dickinson and Company, Franklin Lakes, NJ, USA), and PBMC were isolated. Whole cell extracts were prepared using Active Motif TM nuclear extract kit (Active Motif, Carlsbad, CA, USA), and activation of NF-κB p65 containing dimers was determined based on selective binding of activated dimers to their consensus binding sites in immobilized oligonucleotides, using the TransAM® NF-κB family kit (Active Motif, Carlsbad, CA, USA), as recently described in detail [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, 18 have shown significant changes in leptin level across different phases of the menstrual cycle [16][17][18][19][20]23,24,[31][32][33][34][35][36][37][38][39]41,43 (Table 1), while four studies reported no changes in leptin throughout the menstrual cycle 27,28,42,44 (Table 2). Most of the studies reported significant changes in leptin and showed a steady increment from the lowest level at the early follicular phase to its peak at late luteal phase-except two studies, where leptin peak was detected at the mid-cycle phase near the time of LH surge.…”
Section: Variation Of Leptin During Menstrual Cyclementioning
confidence: 99%